2011
DOI: 10.1007/s12016-011-8293-8
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Epigenetics in Autoimmune Diseases

Abstract: A variety of mechanisms have been suggested as the means by which infections can initiate and/or exacerbate autoimmune diseases. One mechanism is molecular mimicry, where a foreign antigen shares sequence or structural similarities with self-antigens. Molecular mimicry has typically been characterized on an antibody or T cell level. However, structural relatedness between pathogen and self does not account for T cell activation in a number of autoimmune diseases. A proposed mechanism that could have been misin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 170 publications
(102 reference statements)
0
86
0
Order By: Relevance
“…The concept of Bmolecular mimicry^asserts that antigens circulating in blood following infection by viruses or bacteria can (in some people) prompt the development of antibodies recognizing human proteins [79]. Using animal models, McClain et al demonstrated that immunization with either a specific EBNA peptide or a very similar SSA 60 (Ro) peptide will lead to the formation of anti-SSA 60 antibodies and these animals eventually acquire symptoms characteristic of lupus [80].…”
Section: Periodontal Infections Smoking and Aplmentioning
confidence: 99%
“…The concept of Bmolecular mimicry^asserts that antigens circulating in blood following infection by viruses or bacteria can (in some people) prompt the development of antibodies recognizing human proteins [79]. Using animal models, McClain et al demonstrated that immunization with either a specific EBNA peptide or a very similar SSA 60 (Ro) peptide will lead to the formation of anti-SSA 60 antibodies and these animals eventually acquire symptoms characteristic of lupus [80].…”
Section: Periodontal Infections Smoking and Aplmentioning
confidence: 99%
“…Indeed, HDACIs are currently the most widely studied epigenetic therapeutics for treating inflammatory diseases because they are orally active, safe, and well tolerated at low doses [135]. When histone modification was studied in autoimmune diseases, global H3 and H4 hypoacetylation and hypermethylation were found in CD4+ T cells from SLE patients, accompanied with the decreased level of HATs [152].…”
Section: Histone Modificationmentioning
confidence: 99%
“…A growing number of studies both in patients and experimental models propose that epigenetic regulation may hold the key to a better understanding of the initiation and progression of autoimmune diseases. More specifically, studies demonstrating the impact of epigenetic changes in systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), type 1 diabetes (T1D), multiple sclerosis (MS), and other autoimmune diseases have been published [62,135,82,88,136].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, such changes of gene expression can be mediated by environmental factors (e.g. diet, smoking, infectionsall of which have been implicated in CD aetiology), and can occur within an individual's lifetime subsequently persisting for multiple generations [ 11 ]. One example of epigenetics is a study that examined rectal biopsies, which found that the gene ULK1 was methylated only in patients with CD [ 12 ].…”
Section: Geneticsmentioning
confidence: 99%